2004
DOI: 10.1016/s0092-8674(04)00302-2
|View full text |Cite|
|
Sign up to set email alerts
|

IκB Kinase Promotes Tumorigenesis through Inhibition of Forkhead FOXO3a

Abstract: Nuclear exclusion of the forkhead transcription factor FOXO3a by protein kinase Akt contributes to cell survival. We investigated the pathological relationship between phosphoylated-Akt (Akt-p) and FOXO3a in primary tumors. Surprisingly, FOXO3a was found to be excluded from the nuclei of some tumors lacking Akt-p, suggesting an Akt-independent mechanism of regulating FOXO3a localization. We provide evidence for such a mechanism by showing that IkappaB kinase (IKK) physically interacts with, phosphorylates, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
605
1
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 808 publications
(641 citation statements)
references
References 20 publications
24
605
1
11
Order By: Relevance
“…PDK1 constitutively and moderately activates NF-B through phosphorylation of IKK␤ under nonstimulating conditions, whereas Akt is involved in strong NF-B activation through IKK␣ only when cells are stimulated with TNF-␣. Recently, Hu et al (36) reported a novel cross-talk between the IKK/NF-B and PI3K/PDK1/Akt pathways. They showed that IKK␤ phosphorylated and caused proteolysis of the Forkhead family transcription factor FOXO3a (FKHRL1), which was known to be phosphorylated and excluded from nuclei by Akt (37).…”
Section: Discussionmentioning
confidence: 99%
“…PDK1 constitutively and moderately activates NF-B through phosphorylation of IKK␤ under nonstimulating conditions, whereas Akt is involved in strong NF-B activation through IKK␣ only when cells are stimulated with TNF-␣. Recently, Hu et al (36) reported a novel cross-talk between the IKK/NF-B and PI3K/PDK1/Akt pathways. They showed that IKK␤ phosphorylated and caused proteolysis of the Forkhead family transcription factor FOXO3a (FKHRL1), which was known to be phosphorylated and excluded from nuclei by Akt (37).…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, Hu et al (2004) have shown that IKKb activation in breast cancer cells promotes cell proliferation and suppresses apoptotic potential through phosphorylation and degradation of the proapoptotic factor Foxo3a.…”
Section: Apoptosis Evasionmentioning
confidence: 99%
“…However, there is also evidence that an Akt-independent mechanism of FOXO3a regulation exists. In vitro co-transfection of FOXO3a and IKK resulted in strong inhibition of FOXO3a activity independent of Akt [13].…”
Section: Introductionmentioning
confidence: 97%